2003
DOI: 10.1177/089686080302302s32
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis against Gram-Positive Organisms Causing Exit-Site Infection and Peritonitis in Continuous Ambulatory Peritoneal Dialysis Patients by Applying Mupirocin Ointment at the Catheter Exit Site

Abstract: Objective We evaluated the effectiveness of local application of mupirocin ointment at the catheter exit site in preventing exit-site infection and peritonitis attributable to gram-positive organisms in continuous ambulatory peritoneal dialysis patients. Methods This prospective randomized controlled trial included 154 patients. They were randomly allocated to a mupirocin-treated group (group M) and a control group (group C). Group M included 73 patients (47.4%) who were instructed to apply mupirocin ointment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…Thus, nine studies were evaluated: a prospective double-blind randomized controlled trial [ 16 ] and eight randomized clinical trials [ 17 – 24 ]. All studies were evaluated and classified as having a low risk of bias and adequate methodological quality by the Cochrane referential [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, nine studies were evaluated: a prospective double-blind randomized controlled trial [ 16 ] and eight randomized clinical trials [ 17 – 24 ]. All studies were evaluated and classified as having a low risk of bias and adequate methodological quality by the Cochrane referential [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between age and peritonitis has been inconsistent in various reports. Local application of mupirocin ointment at the catheter exit site can prevent exit-site infection and peritonitis involving gram-positive organisms (14). In the present long-term Peritonitis is the most important complication of chronic PD, causing significant morbidity and mortality (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…52 Subsequent studies have confirmed these results. [53][54][55][56][57][58][59] Over time, implementation of this protocol in our program has almost eliminated both S. aureus exit-site infections and peritonitis, indicating that most S. aureus peritonitis is derived from S. aureus at the exit site ( Figure 2). Review articles have evaluated the efficacy of various antibiotic prophylaxis protocols at the exit site.…”
Section: Pd Catheter Insertion and Immediate Postoperative Carementioning
confidence: 99%